(untitled) (Journal of the College of Basic Education, 2024)
The research study aimed to identify the relationship between psychological endurance and its relationship to some psychological skills among college basketball team players. The researcher used the descriptive approach to suit the research. Here, the research problem focused on the existence of a discrepancy in the level of their psychological skills during skill performance, so the research sample was chosen ( 16 players) from the basketball team of the College of Physical Education and Sports Sciences / Al-Mustansiriya University. The researcher assumed that there are significant differences between endurance and some psychological skills among the players of the college basketball team. The researcher showed the conclusion from the research that the psychological aspect is a very important factor for them in performing skills. Basketball: There is a significant correlation between psychological endurance, motivation, self-confidence and anxiety in sports competition among members of the research sample. The researcher recommended reducing psychological difficulties and trying to reduce their intensity and remove them through good sports performance and focusing on psychological and physical training during their training in order to reach the highest performance in The competition.